Nickel Integrated Carbon Electrodes for Improved Stability. Issue 13 (22nd September 2020) - Karajagi, Imran; K., Ramya; Ghosh, P. C.; Sarkar, A.; Rajalakshmi, N.
Abstract : The development of an efficient, stable and low cost air electrode is a necessity in metal-air battery for oxygen reduction and oxygen evolution reaction. Carbon based air electrodes are conventionally used in metal-air batteries due its high electrical conductivity, high specific surface area and porosity. However, the highly oxidative environment of metal-air batteries during charging, corrodes the carbon air electrodes which lead to poor cyclic stability. The current study develops a hybrid air electrode with a nickel interlayer between carbon and electrocatalyst. This approach protects the carbon from corrosion and also provides an enhanced electocatalytic activity for silver catalyst by improving the electron conduction pathway through metallic nickel interlayer. The electroless deposition of nickel interlayer was optimized by deposition time. The electrochemical performances of the electrodes with Zn as anode were investigated to study the stability during cycling. The C–Ni–Ag electrode exhibited a round trip efficiency of 55%, a voltage gap of about 0.9 V over the entire cycle life of more than 1300 cycles and ∼350 h of operation with capacity retention of 98%. These results prove that the Ni interlayer circumvents the carbon corrosion at higher oxidative/charging potentials during oxygen evolution reaction.